APPLICATION OF MYCORRHIZAE IN SUSTAINABLE DATE PALM CULTIVATION - Al-Karaki, Ghazi N (Emirates Journal of Food and Agriculture, 2013)
Date palm (Phoenix dactylifera) is a significant and developing crop especially in the Arabian Peninsula, the Middle East and North Africa regions. The area under cultivation of this tree is increasing annually. Date palms usually grown under harsh and unfavorable growing conditions with low rainfall and high rates of evaporation as well as in soils with low organic matter and nutrient deficiencies. Hence, date palm cultivation becomes dependent on application of high levels of fertilizers as well as on irrigation. This may lead to salinization of soil and leaching of nutrients to deep soils that might affect ground water. Therefore, it is important that date palm plantations are managed in a sustainable way to reduce the impact of date palm cultivation on ecosystems while maximizing dates yield through using such practices as mycorrhizal fungi technology. The application of mycorrhizal fungi technology is an option that can benefit both agronomic plant health and ecosystems. Mycorrhizae confer numerous benefits to host plants including improved plant growth and mineral nutrition, water uptake, tolerance to diseases and stresses such as drought, temperature fluctuation, metal toxicity and salinity. Mycorrhizae may also play a role in the formation of stable soil aggregates, building up a macro porous structure of soil that allows penetration of water and air and prevents erosion. All of these beneficial effects on plant health and soil fitness mean that mycorrhizae have the potential to increase agricultural productivity and are crucial for the sustainable functioning of agricultural ecosystems. This study provides an insight into the application of mycorrhizae in date palm cultivation.